De Charybde de la comptabilité de caisse en Scylla de la comptabilité patrimoniale - Yuri Biondi (Revue de la Régulation)
On the dangerous trip from cash-basis towards accruals-basis by the governmental accounting system in France (and elsewhere).According to the new overarching Law of Finances (LOLF, 2001), the French government has new accounting standards under a new conceptual framework. This reform takes over the business standards and framework whilst trying to cope with specificities of public (non-business) environment. This reform raises then important issues for accounting representation and interpretation of non-business entities.This article aims at analysing this new French “accounting constitution” from a comparative approach that disentangles three distinctive views of business accounting: wealth-basis (static), cash-basis, and accruals-basis (dynamic). In particular, it derives a dynamic accounting model for non-business entities, based on matching expenses with contributions, and in line with their specificities. This dynamic accounting model provides the basis to assess new French accounting standards and framework. Especially the concepts of “produit” (revenue) and “actif” (asset) testify some ambiguity between a static view and a dynamic view, but also the standards from 1 to 7, 10-11 and 13. In this way, our accounting-based analysis of the State as an entity deals with the nature and role of public activities in the economic system and its economic and monetary process.